Nutrition for Musculoskeletal Health - Cesari, Matteo; Marzetti, Emanuele; Cesari, Matteo; Marzetti, Emanuele (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The maintenance of optimal musculoskeletal health is increasingly recognized as a key element for promoting overall health and fostering independent living in advanced age. Growing evidence indicates that nutrition, together with an active lifestyle, plays a central role in supporting musculoskeletal health both aging and in the setting of specific disease conditions. This Special Issue of Nutrients, entitled (3z(BNutrition for Musculoskeletal Health(3y(B, includes original research and review contributions highlighting the relevance of nutrition to musculoskeletal health during aging and in the context of specific diseases. The overarching theme of the Special Issue is addressed through a multidisciplinary set of articles embracing clinical, basic science, and translational studies.s
English
Keywords: Research & information: general; Biology, life sciences; Food & society; lactate; skeletal muscle; hypertrophy; regeneration; muscle satellite cell; amino acids intake; essential amino acids; diet; extended lifespan; mice; bone metabolism; bone mineral density; bone remodelling; citrate supplement; osteopenia; osteoporosis; kidney diseases; amyotrophic lateral sclerosis; Hochu-ekki-to; herbal medicine; muscle dysfunction; motor neuronal cell death; sarcopenia; EWGSOP2; malnutrition; GLIM; SarcoPhAge; nutrition; oral health; older people; swallowing; life course approach; muscle wasting; exercise; kidney disease; aging; muscle; amino acids; metabolism; systemic inflammation; profiling; biomarkers; multi-marker; physical performance; gut microbiota; metabolomics; systems biology; personalized medicine; frailty; precision medicine; metabolic profiling; weight loss; intermittent fasting; fat loss; body composition